Cateslytin and Chromofungin, two CgA derived peptides: actors of the immune and cardiac systems - Scavello, Francesco; Canonaco, Marcello; Angelone, Tommaso; Schneider, Francis; Metz-Boutigue, Marie-Hélène (My University, 2017)
Chromogranin A (CgA) belongs to the granin family of uniquely acidic secretory that are ubiquitous in secretory cells of the nervous, endocrine, immune system. Numerous cleavage products of the granins have been identified, some of these peptides showed biological activities and are costored in secretory granules of different cells. Chromofungin (Chr: CgA47-66) and Cateslytin (Ctl: CgA344–358) are peptides that display antimicrobial activities and activate neutrophils, with important implications in inflammation and innate immunity. Staphylococcus aureus is an opportunistic pathogen and the leading cause of a wide range of severe clinical infections and one of the most important cause of hospital-acquired infections, in fact infections caused by this bacterium have classically an important impact in morbidity and mortality in the nosocomial and community scene. Furthermore, this pathogen is the primary cause of surgical site infections and the most frequently isolated pathogen in Gram-positive sepsis. In the specific field of cardiovascular disease S. aureus leading infective cause of destruction of endocardial tissue after implantation of prosthetic heart valve. This pathogen is also notorious for its ability to resist the available antibiotics and dissemination of various multidrug-resistant S. aureus clones that limit therapeutic options for a S. aureus infection. Aslam et al. in 2013 shown that Ctl is resistant to the degradation of S. aureus protease and is the most antibacterial CgA derived peptide against this bacterium. The aim of study was to evaluate the: 1) Effects of Chr on isolated and Langendorff perfused rat hearts in basal and pathological conditions; 2) In vitro antibacterial activity of a synthetic Cateslytin-derived peptide to cover artificial heart valves and prevent infection by S. aureus; 3) In vivo antibacterial activity of Ctl in rat infected with S. aureus. The first part of the study was performed by using the isolated and Langendorff perfused rat hearts, Elisa assay and real-time PCR. We found that, under basal conditions, increasing doses (11–165 nM) of Chr induced negative inotropic effects without changing coronary pressure. The AKT/eNOS/cGMP/PKG pathway mediated this action. We also found that Chr acted as a postconditioning (PostC) agent against ischemia/reperfusion (I/R) damages, reducing infarct size and LDH level. Cardioprotection involved PI3K, RISK pathway, MitoKATPand miRNA-21. Therefore, we suggest that Chr directly affects heart performance, protects against I/R myocardial injuries through the activation of prosurvival kinases. Results may propose Chr as a new physiological neuroendocrinemodulator able to prevent heart dysfunctions, also encouraging the clarification of its clinical potential. In the second part of the study, two new synthetic peptides containing Ctl (RSMRLSFRARGYGFR) were designed: D*T*Ctl (DOPA-K-DOPA-K-DOPATLRGGE- RSMRLSFRARGYGFR), T*Ctl (TLRGGE-RSMRLSFRARGYGFR) with D*: DOPA-K-DOPA-K-DOPA and T*: TLRGGE. This study is based on the observation of the adhesive properties of the DOPA-K-DOPA-K-DOPA sequence and on the ability of S. aureus endoprotease Glu-C to cleave the TLRGGE sequence. Firstly, using techniques of biochemistry, proteomics (sequencing, mass spectrometry) and microbiology we shown that the digestion by the Glu-C protease of T*Ctl and D*T*Ctl is able to release active Ctl. The prediction analisys of the secondary structure suggested the presence of an alpha helix domain in the case of D*T*Ctl with respect to T*Ctl. The D* group stabilized the secondary structure and facilitated the cleavage by Glu-C to the release of the active peptide Ctl. Subsequently, the effect of the oxidation by NaIO4 of D*T*Ctl on the release of Ctl and the antibacterial activity was analized. Proteomic analysis showed the formation of polymers inhibiting the action of Glu-C and the release of Ctl. We also shown that D*T*Ctl had a MIC value around 75 μM against different strains of S. aureus. This data shown that D*T*Ctl had a direct action against the bacteria without Glu-C cleavage. However, in oxidizing conditions the formation of aggregates of D*T*Ctl reduced the antibacterial action of this synthetic peptide. In the last part of this thesis, we evaluated the in vivo antibacterial activity of Ctl and whether and to which extent Ctl elicit cardioprotection in rat infected with S. aureus, as a model of infection with this bacterium. Identification of specific molecular targets of tissue and systemic inflammation and damage were analysed by Western blotting, ELISA and microbiological analysis in cardiac homogenates and plasma. A strong reduction of plasma bacterial growth, TNF-α, IL-1β and LDH plasma levels was observed in infected rat treated with Ctl. Western blotting analysis of cardiac extracts showed that Ctl treatment is accompanied by reduction of expression of pro-inflammatory markers, such as iNOS and COX-2. These preliminary data suggest that in vivo Ctl treatment is able to counteract the deleterious effects of S. aureus, and elicits myocardial protection.
Doctorate in “Life Sciences” and Physics and Physical Chemistry” Ciclo XXIX
Keywords: Peptides; Chromogranins